2014
DOI: 10.1371/journal.pone.0113054
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease-Specific Molecules in the Sera Are Linked to Microbe-Associated Molecular Patterns in the Biofilms

Abstract: BackgroundKawasaki disease (KD) is a systemic vasculitis of unknown etiology. The innate immune system is involved in its pathophysiology at the acute phase. We have recently established a novel murine model of KD coronary arteritis by oral administration of a synthetic microbe-associated molecular pattern (MAMP). On the hypothesis that specific MAMPs exist in KD sera, we have searched them to identify KD-specific molecules and to assess the pathogenesis.MethodsWe performed liquid chromatography-mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
1
43
0
1
Order By: Relevance
“…To confirm these findings, we searched for unknown ligands that may activate NOD1 or other vasculitis‐inducing pathways. We first prepared whole extracts and fractionated samples from the sera of KD patients and found that KD sera contain bioactive substances that induce production of IL‐6 and IL‐8 in HCAECs . However, no NOD1‐activating ligands were detected in these KD samples by cell‐based reporter systems or liquid chromatography‐mass spectrometry (LC‐MS) analysis .…”
Section: Kd Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm these findings, we searched for unknown ligands that may activate NOD1 or other vasculitis‐inducing pathways. We first prepared whole extracts and fractionated samples from the sera of KD patients and found that KD sera contain bioactive substances that induce production of IL‐6 and IL‐8 in HCAECs . However, no NOD1‐activating ligands were detected in these KD samples by cell‐based reporter systems or liquid chromatography‐mass spectrometry (LC‐MS) analysis .…”
Section: Kd Aetiologymentioning
confidence: 99%
“…We first prepared whole extracts and fractionated samples from the sera of KD patients and found that KD sera contain bioactive substances that induce production of IL‐6 and IL‐8 in HCAECs . However, no NOD1‐activating ligands were detected in these KD samples by cell‐based reporter systems or liquid chromatography‐mass spectrometry (LC‐MS) analysis . Thus, these results suggest that other innate immune receptor(s) may be associated with the development of KD vasculitis.…”
Section: Kd Aetiologymentioning
confidence: 99%
“…Cervical lymphadenopathies in KD patients may implicate the entry of causative agents or their derived substances (pathogen-associated molecular patterns) leading to the systemic vasculitis [11]. CD4 + T-cell proliferation in the interstitium of KD tonsils in the index case may account for active antigen presentations and reactive lymphoproliferation in these areas [6].…”
Section: Discussionmentioning
confidence: 99%
“…This heterophilic adhesion mediates bacterial phagocytosis by neutrophils, and is involved in the initial tethering of granulocytes to E-selectin on the endothelium prior to their transendothelial migration during inflammatory responses [14]. From this view point, certain pathogen-associated molecular patterns might shape the tonsillar pathology during the acute phase of KD [11,15,16]. The tonsilla palatina is a primitive lymphoid organ, where the innate and acquired immunocytes interacts in the milieu on the direct contact to environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation